A protective role for FADD dominant negative (FADD‐DN) mutant in trinitrochlorobenzene (TNCB)‐induced murine contact hypersensitivity reactions. (26th December 2017) - Zhang, X.; Han, Y.; Song, L.; Huo, L.; Lai, X.; Zhang, Y.; Zhang, J.; Hua, Z.
Summary: Background: Fas‐associated protein with death domain (FADD) is a classic adaptor protein in apoptosis. Increasing evidence has shown that FADD is also implicated in T‐cell development, activation and proliferation. The role of FADD in inflammatory disorders remains largely unexplored. Aim: To assess the role of FADD in inflammatory disorders. Methods: We established an experimental model of contact hypersensitivity (CHS) by using 2, 4, 6‐trinitrochlorobenzene (TNCB) on transgenic mice expressing a dominant negative mutant of FADD (FADD‐DN), Results: CHS responses were clearly attenuated in FADD‐DN mice compared with control mice. In the retroauricular lymph nodes, the ratio of CD8+ T cells was also decreased. Conclusion: FADD‐DN appears to play a protective role in TNCB‐induced CHS reactions.